Innovative teaching strategies in higher education: active learning and competencias a systematic review - Gonzales-Zarpan, Luis Miguel; Pisfil-Benites, Nilthon (LACCEI, 2025)
Higher education faces the challenge of training professionals capable of responding to the demands of a dynamic working world. In this context, innovative teaching strategies prioritize active learning and the development of key competencies. Methodologies such as flipped classroom, gamification and project-based learning (PBL) seek to overcome traditional methods through interaction, collaboration and practical application of knowledge. This systematic literature review (SLR) analyzes recent (2019-2023) scientific production in Scopus, employing the PRISMA methodology and the PICO model. The results show that the flipped classroom strengthens self-regulation, gamification improves motivation and retention, and PBL fosters critical thinking and collaboration. It is concluded that these strategies optimize university education and suggest exploring their impact on the employability of graduates